Study Concerning Phytosanitary Treatments in Deciduous Forests - Pop, Dacian (Proenvironment, 2016)
The pine forests installed on degraded land are subject of a multitude of pests and pathogens attacks. The aimour study is to reveal the variety of attacks in a pine tree forest during a tree year’s period, 2012, up to 20espectively. Data were processed with STATISTICA v7.0. The pests belonging Leucaspis sp. are most susceptible climatic factors (R = 0.329), being favored by temperatures of 4-20 ° C and humidity in the range 55-85ºC, while ensitive is Calomicrus pinicola (R = 0.223), but its action is, however, favored by the temperature and humidanging from 25-50%, and 4-18ºC, respectively.